Molecular Pathology in Clinical Practice - Leonard, Debra G.B (Springer New York : Imprint: Springer, 2007)
Molecular Pathology in Clinical Practice addresses all areas of molecular pathology clinical practice in a single text, including: molecular biology basics, genetics, infectious diseases, hematopathology, solid tumors, HLA typing, identity testing and laboratory management. This text will provide a comprehensive reference for molecular pathologists as well as the practicing molecular pathologist and trainees. Includes 189 illustrations, 45 in color. Debra G.B. Leonard, MD, PhD is Professor and Vice Chair of Laboratory Medicine, Department of Pathology and Laboratory Medicine at Weill Medical College of Cornell University and New York Presbyterian Hospital, New York, NY. .